Participant observation for inquiry-based learning: a document analysis of exam papers from an internship-course for master’s students in health services research in Germany - Ullrich, Charlotte; Ziegler, Sandra; Armbruster, Alicia; Wensing, Michel; Klafke, Nadja (BMC medical education, 2024)
Inquiry-based learning (IBL) is a type of problem-based learning. While IBL aims at reflecting the work of practicing researchers, only some students will pursue an academic career. We therefore designed a course that provides opportunities for IBL by applying participant observation to internship work experience inside and outside academia. Using this internship course as an example, we investigated, how master’s students in health science executed an IBL assignment regarding the application of participant observation and presentation of findings. In addition, the understanding of occupational fields provided through the IBL assignment was examined.